2016
DOI: 10.1093/ofid/ofw175
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Analog NITD008 Is a Potent Inhibitor of Zika Virus

Abstract: The ongoing Zika virus (ZIKV) outbreaks have raised global concerns due to its unexpected clinical manifestations. Antiviral development is of high priority in response to the ZIKV emergency. In this study, we report that an adenosine analog NITD008 has potent in vitro and in vivo antiviral activity against ZIKV. The compound can effectively inhibit the historical and contemporary ZIKV strains in cultures as well as significantly reduce viremia and prevent mortality in A129 mice. Our results have demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
101
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(110 citation statements)
references
References 16 publications
6
101
0
1
Order By: Relevance
“…Current small-molecule drugs against flaviviruses include NITD008, a nucleoside analog targeting viral polymerases that has been shown to exhibit potent antiviral activity against DENV, WNV, hepatitis C virus, and, more recently, ZIKV in Vero cells (22,23). Therefore, we next evaluated if this drug can block ZIKV replication in HSeCs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Current small-molecule drugs against flaviviruses include NITD008, a nucleoside analog targeting viral polymerases that has been shown to exhibit potent antiviral activity against DENV, WNV, hepatitis C virus, and, more recently, ZIKV in Vero cells (22,23). Therefore, we next evaluated if this drug can block ZIKV replication in HSeCs.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, our data demonstrating the dose-dependent effect of a well-tested antiflavivirus compound, NITD008, on blocking ZIKV replication in SCs are encouraging and warrant future in vivo studies to test whether this drug can cross the SCB and clear testicular ZIKV infection. A recent study reported the inhibition of ZIKV by NITD008 in Vero cells and in a mouse model; however, that study did not examine the ability of this drug to clear testicular infections (22). Our in vitro model of the SCB not only can be used as a tool to characterize testicular infections by other viruses, including Ebola virus, but also will allow the rapid testing of new antiviral drugs to cross the SCB and mitigate infection in the seminiferous tubules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The in vitro antiviral activity of temoporfin to a contemporary ZIKV strain GZ01 [72] (isolated from patient returned from Venezuela in 2016) was carried out as previously described [73]. Briefly, Vero cells were infected with Zika virus GZ01/2016 strain at a MOI of 0.1 and treated with 10-fold serial dilutions of temoporfin.…”
Section: Viral Titer Reduction Assaysmentioning
confidence: 99%
“…Three studies have used susceptible AG129 or A129 mice to demonstrate that compounds targeting the viral RNA-dependent RNA polymerase (RdRp) can reduce the viral burden in tissues and reduce or delay virus-induced morbidity and mortality following inoculation of ZIKV (29,30,83). In addition, treatment for 1 week with sofosbuvir, an RdRp inhibitor approved by the Food and Drug Administration for the treatment of hepatitis C virus infection (84), beginning 1 day after infection with a mouse-adapted strain of ZIKVDakar 41519 improved the survival rate of C57BL/6 mice treated with an anti-IFNAR1 MAb (85).…”
mentioning
confidence: 99%